Chronic Total Occlusion Percutaneous Coronary Intervention in Patients With Prior Coronary Artery Bypass Graft: Current Evidence and Future Perspectives - Guo, Lei; Lv, Haichen; Yin, Xiaomeng (Frontiers in Cardiovascular Medicine, 2022)
Coronary chronic total occlusion (CTO), which occurs in 18.4-52% of all patients referred for coronary angiography, represents one of the last barriers in coronary intervention. Approximately half of all patients with prior coronary artery bypass graft (CABG), who undergo coronary angiography, are diagnosed with coronary CTO. In fact, these patients often develop recurrent symptoms and events, necessitating revascularization. Currently, there is neither a consensus nor developed guidelines for the treatment of CTO patients with prior CABG, and the prognosis of these patients remains unknown. In this review, we discuss current evidence and future perspectives on CTO revascularization in patients with prior CABG, with special emphasis on clinical and lesion characteristics, procedural success rates, periprocedural complications, and long-term outcomes.